Mestres dos Mestres: políticas patrimoniais e expressões culturais de matriz africana em Laranjeiras (SE) - Clovis Carvalho Britto; Paulo Brito do Prado (Ciências Sociais Unisinos)
The paper presents the Brazilian heritage policies with emphasis on the appreciation of the cultural diversity and cultural heritage of the expressions of African origin, discussing projects, tensions and paradoxes. The investigation of aspects of the “patrimonialization” of the guardians of the quilombola memory in Laranjeiras (Sergipe State) discusses the development of public policies concerned with the symbolic value of the Brazilian cultural heritage and its conceptual expansion – as presently perceived and understood – as a result of the crossing of elements that constitute the material and immaterial culture.